British urban form in twentieth-century Brazil - Rego, R.L.; Meneguetti, K.S. (Urban Morphology, 2007)
A number of new towns were created in northern Paraná State, Brazil, by the British company Parana Plantations as part of a colonization scheme in the first half of the twentieth century. The urban landscapes created by these towns are distinct from those associated more generally with the colonization of Brazil. However, there has been no extended analysis of their origin, organization, conformation and impact. Drawing on contemporary sources, this task is attempted here. Set within a broader context, a systematic colonization is revealed in relation to its British colonial background. The layouts of the towns founded by Parana Plantations show many features of a British colonial town model. The colonization scheme reflects some of the garden city tenets that were circulating widely in the colonial world.